القواعد الفقهية الإسلامية و الدولية للإضراب : دراسة فقهية إسلامية مقارنة في المواثيق الدولية - Samia Silabdi; Muhamed Tahir Sabit; Ahmed Kamal Nik Mahmod (al-Afkar, Journal For Islamic Studies, 2021)
Islamic jurisprudence is interested in the development of Islamic judicial rules on labor strikes using Islamic judicial rules and others in the field of labor strikes, but these rules are still rare and are not applied in pacts and charters between Muslim countries, nor in artificial laws. despite the importance of these rules in solving workers' problems. This is clear from international conventions.